SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN CALON MAHASISWA BARU JALUR PRESTASI DI SEKOLAH TINGGI TEKNOLOGI ADISUTJIPTO MENGGUNAKAN SIMPLE MULTI ATTRIBUTERATING TECHNIQUE - Honggowibowo, Anton Setiawan (Sekolah Tinggi Teknologi Adisutjipto, 2015)
In the era of globalization, educational institutions are required to follow the development of information technology. Information technology required and can be applied as a decision support tool managerial activities at the college. This research aims to develop a decision support system for the Sekolah Tinggi Teknologi Adisutjipto (STTA), namely the acceptance of new students, especially the path of achievement, using the Simple Multi Attribute Rating Technique of Web based, where in the method is choosing alternative criteria that have value and weight has been determined, getting the new students he deserves. Based on the results of testing the system, it was concluded that the method is Simple Multi Attribute Rating Technique is effective enough to be applied in determining the admission of new students in STTA.